The Effect of Science Kit and Supervision Models on The Implementation and Implications on The Evaluation of Science Practicum Distance Learning - A.A. Ketut Budiastra; Iwan Wicaksono; Nia Erlina (Jurnal Penelitian Pendidikan IPA, 2022)
The implementation of science practicum is one of the challenges in the open distance education system. The purpose of this research is to examine the effect of the Kit IPA variable and the pattern of guidance on the implementation and evaluation of Science Practicum activities in Distance Learning. The type of research in this study is an explanatory research with a quantitative approach involving a number of 306 students who have taken the Science Practicum course in the Elementary School Teacher Education program. Respondents' responses were analyzed using a Likert scale and data analysis using the Structural Equation Model (SEM). The results of the data have met the Model Suitability Test (Goodness of Fit Test) which includes: Science Kit and Guidance Patterns have a significant effect on Practicum Implementation. Guidance pattern has a significant effect on practicum evaluation, but Kit IPA and practicum implementation have no significant effect on practicum evaluation. The implication of this research is that it provides the potential for improvement in the implementation of science practicum in distance education due to the needs of the educational community.